INNOVATIVE TECHNOLOGIES IN DEVELOPING ECOLOGICAL CULTURE AMONG FUTURE EFL TEACHERS - Sadullayeva Zukhra Murodullayevna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract:   This article examines the pedagogical role of innovative technologies in developing ecological culture among future EFL teachers within higher education. The study emphasizes the significance of digital learning environments, interactive platforms, and technology-enhanced pedagogical practices in promoting ecological awareness, sustainability-oriented thinking, and environmentally responsible communication. The findings demonstrate that innovative technologies create favorable conditions for reflective learning, collaborative interaction, and sustainability-oriented educational engagement among future English language teachers. The research substantiates the necessity of integrating technology-mediated ecological education into contemporary EFL teacher preparation.
Keywords: Keywords: innovative technologies, ecological culture, EFL teacher education, digital pedagogy, sustainability-oriented learning, educational technologies.